Peran Mediator Dinas Tenaga Kerja Kota Medan dalam Memberikan Perlindungan Hukum Akibat Pemutusan Hubungan Kerja - Limrogate Immmanuel; Taufik Siregar; M. Citra Ramadhan (Mahesa Research Center, 2021)
The purpose of this research is to study and analyze the legal arrangements of Industrial Relations Mediators in solving layoffs, the role of the Medan City Disnaker Mediator in providing legal protection for workers' rights due to layoffs and the obstacles faced by the Medan City Manpower Office in providing legal protection for their rights. workers due to layoffs. Research on the role of the Medan City Manpower Office Mediator in providing legal protection due to layoffs is a normative juridical research. Normative legal research aims to examine library legal materials. The results show that the existence of legal arrangements regarding industrial relations mediators which are regulated in the Minister of Manpower Regulation Number 17 of 2014 concerning the Appointment and Dismissal of Industrial Relations Mediators as well as Mediation Work Procedures and Regulation of the Minister for Empowerment of State Apparatus Number 06 of 2009. In the role and process of enforcement the law enforced by the Medan City Manpower and Transmigration Mediators for workers / laborers who have been laid off is influenced by aspects that affect law enforcement, consisting of: legal substance aspects (laws), law enforcement aspects, facilities and infrastructure aspects, community aspects, aspects culture. The obstacles faced by the Mediator of the Medan City Manpower Office for workers or laborers who were laid off can be seen from the aspects that affect law enforcement.